2018
DOI: 10.1159/000494831
|View full text |Cite
|
Sign up to set email alerts
|

Biology-Based Surgery: The Extent of Lymphadenectomy in Cancer of the Colon

Abstract: The progression of colon cancer (CC) involves hematogenous and lymphatic spread to locoregional lymph nodes (LN), distant LN, and metastatic sites including the liver. The biological mechanisms that govern CC progression remain elusive. The Halsted model assumes an orderly, stepwise progression from the primary tumor to nearby nodes, henceforth to anatomically more distant nodes, and ultimately to distant organs. The Fisher model, on the other hand, regards the release of metastatic cells as early and essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In addition to the radicality of the resection, nodal yield is influenced by tumour (tumour size, T stage, tumour infiltrating lymphocytes, differentiation, immune response, microsatellite instability high phenotype), institution (hospital size, method of specimen pathological processing) and patient factors (age, body mass index, concurrent gastrointestinal pathology). [66][67][68] Given the high risk of bias of currently available data, large randomized trials are required to assess the oncological benefit of CME with CVL/D3 dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the radicality of the resection, nodal yield is influenced by tumour (tumour size, T stage, tumour infiltrating lymphocytes, differentiation, immune response, microsatellite instability high phenotype), institution (hospital size, method of specimen pathological processing) and patient factors (age, body mass index, concurrent gastrointestinal pathology). [66][67][68] Given the high risk of bias of currently available data, large randomized trials are required to assess the oncological benefit of CME with CVL/D3 dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of tumour biology, immune responses and neoadjuvant chemotherapy on lymph node yield and oncological outcomes 49,65 are difficult to control for in observational studies and a casual relationship has not been conclusively demonstrated. In addition to the radicality of the resection, nodal yield is influenced by tumour (tumour size, T stage, tumour infiltrating lymphocytes, differentiation, immune response, microsatellite instability high phenotype), institution (hospital size, method of specimen pathological processing) and patient factors (age, body mass index, concurrent gastrointestinal pathology) 66–68 . Given the high risk of bias of currently available data, large randomized trials are required to assess the oncological benefit of CME with CVL/D3 dissection.…”
Section: Discussionmentioning
confidence: 99%
“…They attribute this to occult micro-metastases or isolated tumor cells and recommend broadening the indication for post-operative chemotherapy to include these cases. To this end, CME with standardized CVL would improve accurate nodal staging by including more conventionally negative LNs that could harbor micro-metastases and isolated tumor cells, in order to categorize patients for adjuvant treatment [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Halsted model, progression of metastasis occurs in a stepwise fashion from the primary tumor to pericolic, intermediate, and central nodes and ultimately to distant organs. In the Fisher model, metastatic progression is non-linear and can bypass proximal nodal basins altogether [30][31][32][33]. Pattern of nodal spread has different implications on the theoretical impact of radical D3 lymphadenectomy.…”
Section: Impact Of Cme On Mesocolic Dissection Gradementioning
confidence: 99%